Margin Analysis and Marketing Efficiency of Bali Cattle Post Covid-19 Pandemic - Ayu Gemuh Rasa Astiti, Ni Made (Green Publisher Indonesia, 2022)
This research is a literature study on margins and marketing efficiency. This study aims to analyze the margins and marketing efficiency of Bali cattle post covid-19 pandemic. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data are obtained through library research techniques (library study) which refers to sources available both online and offline such as scientific journals, books, and news sourced from trusted sources. The results of the study concluded that based on the marketing margin, farmer's share, and the efficiency of the marketing channel pattern that had been carried out, it was concluded that the Bali cattle marketing system was efficient. This can happen because it is influenced by several factors, namely the general condition of Bali cattle business actors.